2016
DOI: 10.1142/s1793962316500136
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of environmental pollution intensified by urbanization on human population

Abstract: A mathematical model is presented here to investigate the effects of environmental pollution, intensified by urbanization, on the density of human population. Here, urbanization is assumed to grow with constant rate and also, induced through growing population and the corresponding population pressure. The model analysis, qualitatively and numerically, show that though the growth of population or population pressure is responsible for the growing urbanization, but for very large increase of urbanization, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Environmental pollution is typical of not only industrial and densely populated territories [1][2][3], but also tourism-important landscapes [4][5][6] and protected areas [7,8]. A novel category of public establishments, which share touristic and conservation features, has appeared recently, namely, geoparks [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollution is typical of not only industrial and densely populated territories [1][2][3], but also tourism-important landscapes [4][5][6] and protected areas [7,8]. A novel category of public establishments, which share touristic and conservation features, has appeared recently, namely, geoparks [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they suggested for sustainable mining through control measures imposed by the government on mining activities. Unprecedented urbanization, which also degrades the environment, is also incorporated in a nonlinear modeling study undertaken by Tandon and Jyotsna (). In this study, they investigated the impact of pollution, intensified by urbanization, on human population.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have been recognized as effective tools to analyze the interactive dynamics of growing population and various development activities like industrialization and urbanization with forest ecosystems. In this direction, various investigations have been carried out through the use of nonlinear mathematical models involving dynamical variables (Agarwal, Fatima, & Freedman, ; Dubey, , ; Dubey & Das, ; Dubey & Hussain, ; Dubey, Upadhyay, & Hussain, ; Dubey, Sharma, Sinha, & Shukla, ; Misra & Lata, ; Misra, Lata, & Shukla, , ; Shukla et al., ; Shukla, Lata, & Misra, ; Shukla, Misra, Agarwal, & Shukla, ; Tandon & Jyotsna, ). However, there are very few studies related to mathematical modeling, which take into account the role of wildlife population on forest ecosystems (Agarwal et al., ; Agarwal & Pathak, ).…”
Section: Introductionmentioning
confidence: 99%